Recursion; Early; Language; Lear The Significances of Recursion in Early Language Learning: The Study of Psycholinguistics - Zumam, Wildona; Amiruddin, Mohammad; Ramadhani , Nilam (LPPM Press, 2024)
This study is to finding out the significances of recursion in early language learning. This study is a qualitative research by using descriptive case study approach. This study describes in details the significances of recursion in early on language acquisition. The participants of this study are 44 participants. Observation and interview are conducted to get the data of the significance of recursion in early language development. Furthermore, the elements of the inquiry examine how recursion affects their capacity to offer feedback. The results show that recursion is important for overcoming stimulus poverty in a second language and producing sentences. According to 16 (36%) of the participants, the recursion notion can address the lack of stimuli in language acquisition. Whereas 28 (64%) of participants claim they can produce sentences because their lecturers apply recursion ideas. It is used to drill and reinforce the supplied input. Students can use their existing knowledge to address language learning challenges since teachers have repeatedly offered a procedure.